Boundary objects for value-based requirements engineering - Paech, Barbara; Aurum, Aybüke (SIGSAND-EUROPE 2008, 2008)
Value-based requirements engineering focuses on the alignment of requirements engineering decisions and business value decisions. There is much evidence on the importance of this alignment and there are several approaches for tackling specific alignment decisions such as e.g. release planning. However, for the general picture of what this alignment is about, a common language between requirements engineering and business decision makers is needed. The goal of this paper is to make explicit the boundary objects between requirements engineering and business value decisions. These boundary objects have been derived from literature and are evaluated in three typical scenarios of how software can provide value to business: (1) the product management scenario, where software is (part of) a product sold by the company, (2) the IT procurement scenario where the software and related services are procured by the company, and (3) the IT development scenario, where software is developed in-house to be used in the IT infrastructure of the company. An empirical study of the relevance of the identified boundary objects is the most important future work.
Gesehen am 10.06.2020